2017
DOI: 10.1111/lam.12764
|View full text |Cite
|
Sign up to set email alerts
|

The distinguishing effects of low-intensity electromagnetic radiation of different extremely high frequencies on Enterococcus hirae : growth rate inhibition and scanning electron microscopy analysis

Abstract: A stronger inhibitory effect of low-intensity electromagnetic field on Enterococcus hirae ATCC 9790 bacterial growth rate was observed with 53 GHz vs 51·8 GHz, regardless of exposure duration. Scanning electron microscopy analysis showed that almost all irradiated cells in the population have spherical shapes similar to nonirradiated ones, but they have increased diameters in case of irradiated cells at 53 GHz, but not 51·8 GHz. The results are novel, showing distinguishing effects of low-intensity electromagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The bacterial suspension was irradiated by EMI generator; model G4‐141 (State Scientific‐Production Enterprise ‘Istok’, Fryazino, Moscow Region, Russia) which emits (through conical antenna) coherent in time electromagnetic waves with the frequencies of 51·8 GHz and 53 GHz with 1 Hz frequency of amplitude modulation (frequency stability was 0·05%); the flux capacity was 0·06 mW cm −2 , as described before (Soghomonyan and Trchounian ; Hovnanyan et al . ). EMI with this amount of flux capacity has no effect on the temperature of bacterial suspension during irradiation: the change in temperature of suspension is below 0·1°C during the exposure.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…The bacterial suspension was irradiated by EMI generator; model G4‐141 (State Scientific‐Production Enterprise ‘Istok’, Fryazino, Moscow Region, Russia) which emits (through conical antenna) coherent in time electromagnetic waves with the frequencies of 51·8 GHz and 53 GHz with 1 Hz frequency of amplitude modulation (frequency stability was 0·05%); the flux capacity was 0·06 mW cm −2 , as described before (Soghomonyan and Trchounian ; Hovnanyan et al . ). EMI with this amount of flux capacity has no effect on the temperature of bacterial suspension during irradiation: the change in temperature of suspension is below 0·1°C during the exposure.…”
Section: Methodsmentioning
confidence: 97%
“…These frequencies are of interest due to numerous results with lactobacilli and other bacteria reported before (Soghomonyan and Trchounian , ; Hovnanyan et al . ) and that these frequencies are suggested to be resonant for water molecules and might change water properties facilitating effects of EMI on bacteria (Torgomyan and Trchounian ; Soghomonyan et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested this could be due to the MMW activation of bacterial DNA repair mechanisms. Other studies by an Armenian research group reported a reduction in E. coli cell growth when exposed to MMWs [39][40][41][42][43][44][45]. These studies reported that when E.coli cultures were exposed to MMWs in the presence of antibiotics, there was a greater reduction in the bacterial growth rate and an increase in the time between bacterial cell division compared with antibiotics exposure alone.…”
Section: Cell Proliferationmentioning
confidence: 94%
“…It has also been demonstrated that an electromagnetic wave irradiation for 5 s at 500-1000 kHz has bactericidal activity against several oral bacterial pathogens including E. faecalis [32]. In addition, several studies of extremely high frequencies EMF effect on Enterococcus hirae resulted in a decreased specific growth rate, but suggesting the differences in mechanisms of action [20,30,11].…”
Section: Effect Of the Exposure Time And The Conductivity Of The Medimentioning
confidence: 99%